MR 4log and low levels of NK cells are associated with higher molecular relapse after imatinib discontinuation: Results of a prospective trial. (February 2021) - Seguro, Fernanda S.; Maciel, Felipe V.R; Santos, Fernanda M.; Abdo, André N.R.; Pereira, Thales D.M.; Nardinelli, Luciana; Rocha, Vanderson; Bendit, Israel
Highlights: Therapy-free survival was 54 % after 24 moths of imatinib discontinuation. MR4 was associated with higher risk of molecular relapse. NK cells proportion is lower in patients with MR4. Abstract: Background: Treatment-free survival (TFS) in chronic myeloid leukemia (CML) is a new goal. This prospective study aims to evaluate imatinib discontinuation's feasibility and safety in patients with deep molecular response MR4 (BCR-ABL1 < 0.01 % IS). Methods: Study was approved by the ethical committee and registered at Clinicaltrials.gov (NCT03239886). Incluision criteria were: age ≥ 18y, chronic phase, first-line imatinib for 36 months, MR4 for 12 months, no previous transplant or resistance. Imatinib was resumed when two samples confirmed the loss of MMR. The primary endpoint was molecular recurrence-free survival (MRFS) at 24 months. Lymphocyte subpopulations were counted in peripheral blood before discontinuation. Results: 31 patients were included from Dec/2016 until Oct/2017. Median age was 54years, 58 % male, 58 % low Sokal, 65 % b3a2 transcripts, and 61 % were in MR4.5. Imatinib therapy's median time was 9.7y (3−14.9 y), median time of MR4 was 6.9y (1.6−10.3y). MRFS at 24 months was 55 % (95 % CI 39–75). Thirteen patients relapsed, 46 % after six months of discontinuation, and all patients recovered MMR. Median time to recover MMR was one month. MR4.5 was the only factor associated with MRFS. NK cells proportion at baseline was lower in patients with only MR4 who relapsed after discontinuation. Conclusion: With a median duration of sustained MR4 above five years, as recommended by most TKI discontinuation guidelines, the TFS was similar to previous studies. Only MR4.5 was associated with lower risk of relapse. Further studies are needed to evaluate whether patients with only MR4 and low NK cell levels are suitable for discontinuation.